The chronification mechanism of orofacial inflammatory pain: Facilitation by GPER1 and microglia in the rostral ventral medulla - Zheng, Wenwen; Huang, Xilu; Wang, Jing; Gao, Feng; Chai, Zhaowu; Zeng, Jie; Li, Sisi; Yu, Cong (Frontiers in Molecular Neuroscience, 2023)
Chronic orofacial pain is a common and incompletely defined clinical condition. A new estrogen receptor, G-protein-coupled estrogen receptor 1 (GPER1), has been shown to play an important regulatory role in trunk and visceral pain regulation. Still, its role in orofacial pain has not been fully elucidated. In this study, we investigated the role of GPER1 in the rostral ventral medulla (RVM) during chronic orofacial pain model. The complete Freund's adjuvant (CFA) was injected into rats' bilateral temporomandibular joint cavities to simulate chronic orofacial pain. The behavioral test results show that rats injected with CFA experienced abnormal pain in the orofacial region.Activation of microglia and upregulation of GPER1 and c-Fos significantly. G15 (GPER1 inhibitor) alleviated abnormal orofacial pain and inhibited microglia activation in CFA rats by downregulating the protein content of GPER1 and c-Fos, as well as inhibiting the expression of c-Fos+ and GPER1+ cells. In addition, we found that G15 downregulated the expression of phospholipase C (PLC) and protein kinase C (PKC) and inhibited the expression of GluA1 in the RVM of CFA rats. The experimental results confirmed that GPER1 activation in RVM microglia after CFA injection is involved in the maintenance of chronic orofacial pain through the PLC-PKC signaling pathway. In parallel, we monitored the expression of synapse-associated proteins (PSD-95 and syb-2) in the RVM of CFA rats. The expression of these proteins was significantly upregulated, while the application of G15 led to their downregulation. Combined with the synaptic morphology of neurons in the RVM, as observed by transmission electron microscopy. In summary, GPER1 in RVM microglia is involved in the maintenance of chronic orofacial pain and may be associated with enhanced prominent neuroplasticity via the PLC-PKC pathway.